A strongly polynomial algorithm for criticality of branching processes and consistency of stochastic context-free grammars - Esparza, Javier; Gaiser, Andreas; Kiefer, Stefan (Information processing letters, 2013)
We provide a strongly polynomial algorithm for determining whether a given multi-type branching process is subcritical, critical, or supercritical. The same algorithm also decides consistency of stochastic context-free grammars. •We provide the first strongly polynomial algorithm for criticality of branching processes.•The same algorithm decides consistency of stochastic context-free grammars.•We apply the algorithm to a problem of nuclear physics.